Probiotics, prebiotics, and synbiotics : bioactive foods in health promotion - Watson, Ronald R.; Preedy, Victor R. (Academic Press is an imprint of Elsevier, 2016)
Probiotics, Prebiotics, and Synbiotics: Bioactive Foods in Health Promotion reviews and presents new hypotheses and conclusions on the effects of different bioactive components of probiotics, prebiotics, and synbiotics to prevent disease and improve the health of various populations. Experts define and support the actions of bacteria; bacteria modified bioflavonoids and prebiotic fibrous materials and vegetable compounds. A major emphasis is placed on the health-promoting activities and bioactive components of probiotic bacteria. * Offers a novel focus on synbiotics, carefully designed prebiotics probiotics combinations to help design functional food and nutraceutical products. * Discusses how prebiotics and probiotics are complementary and can be incorporated into food products and used as alternative medicines. * Defines the variety of applications of probiotics in health and disease resistance and provides key insights into how gut flora are modified by specific food materials. * Includes valuable information on how prebiotics are important sources of micro-and macronutrients that modify body functions.--Provided by publisher.